1 - Domination and Resistance: Epidemic and Exile in the German Togoland Colony - Dennis Laumann (Afrika Zamani, 2022)
In 1914, King Dagadu III of Kpandu was forced into exile by the colonial regime in German Togoland. The king’s banishment was the culmination of friction between his royal court and the German colonial administration. The roots of this conflict lay in Germany’s suspicions that Dagadu remained too friendly with his former British allies in the neighboring Gold Coast. Tensions came to the surface, however, with the outbreak an epidemic in Kpandu. The primary charge against Dagadu was that he encouraged resistance to a German vaccina- tion campaign against the spread of sleeping sickness. From the perspective of the people of Kpandu, the vaccination effort itself was to blame for the rising death toll in their town and the disease affecting them was meningitis. This story provides a lens through which to explore how domination and resistance in colonial Africa was played out in the arena of medicine. While the Germans believed their knowledge of health was ‘rational’ and ‘scientific’, the people of Kpandu viewed their colonizers as ignorant bullies who lacked a proper under- standing of local medicine. Based on Ghanaian oral history and German colonial records, this article considers conflicting notions of health and illness and contested spaces of sovereignty in the colonial state.